The Reception of the First Nicene Council by the Church of the East - Vadana, Roby (Asian Horizons, 2025)
The Church of the East originated within the boundaries of Persia and traces its apostolic roots to St Thomas the Apostle. Over the course of its formative four centuries, it developed as an indigenous church in the Persian region. This period was marked by significant trials, as the Church endured persecution under various Sassanian rulers. However, this era of hardship ended during the reign of King Yazdgard, who, akin to Emperor Constantine in the Roman Empire, brought peace and tranquility, allowing free practice of the Christian faith in Persia. At the beginning of the 5th century, Mar Marutha, the bishop of Maiperqat, arrived in Persia as an envoy from the Roman Emperor, which led to the convocation of the Synod of Mar ʼIsḥac in 410. During this synod, the Church of the East accepted the Nicene Creed as well as the canons from the Council of Nicaea brought by Mar Marutha. Subsequently, Mar Acacius of Amid led another significant mission that convened a second Persian synod in 420. In this synod, Mar Acacius brought with him the canons and laws from the Council of Nicaea as well as the canons from various minor Western councils. The Persian bishops accepted all those canons, declaring the unity and universality of the Church. The Church of the East, having endured internal discord and divisions largely due to a lack of established legal and ecclesiastical structures, turned to the Western canons as a means of structured reorganization. The Church sought internal cohesion by formally adopting the Nicene Creed and its accompanying canons and affirmed its commitment to the broader ecclesiastical tradition. Its leading theologians and successive councils would repeatedly emphasise this continuity.